Legal Aspects in Developing Security Systems to Counter Fraud and Manipulation Threats in Online Gambling - Tulkah Husen; Wieke Dewi Suryandari; Tri Susilowati (PT. Publikasiku Academic Solution, 2024)
Online gambling emerges as an endeavor characterized by pecuniary stakes, wherein the operational mechanics and wagering parameters are established by entities overseeing online gambling activities. Facilitated by electronic media and internet connectivity, this milieu offers a platform for the engagement of such pursuits. Supplementing the legal underpinning provided by the Indonesian Criminal Code, Law Number 7 of 1974 concerning the Regulation of Gambling furnishes supplementary provisions governing the conduct of gambling activities. The aim of this reseach is to address the legal aspects in the development of security systems to combat fraud and manipulation threats in online gambling. The process of criminalization ensues with the promulgation of statutes designating certain behaviors, akin to or resembling individual conduct, as proscribed actions subject to punitive reprisals. The research method using normative method legal research. This legislative trajectory culminates in the promulgation of laws prescribing penal sanctions for transgressions. Furthermore, the realm of gambling is subject to regulatory oversight within the purview of Law Number 11 of 2008 about Information and Electronic Transactions (ITE Law). Article 27 paragraph (2) of the aforementioned legislation proffers legal recourse against individuals who, with intent and sans entitlement, disseminate, transmit, or render accessible electronic informational and documentary material imbued with gambling content. Concomitantly, the legal strictures delineated in Article 303 of the Indonesian Criminal Code (KUHP) proscribe gambling activities, imposing penal sanctions that may encompass custodial sentences not exceeding ten